The P2Y12 Receptor Antagonist Ticagrelor Reduces Lysosomal pH and Autofluorescence in Retinal Pigmented Epithelial Cells From the ABCA4-/- Mouse Model of Retinal Degeneration - Lu, Wennan; Gómez, Néstor M.; Lim, Jason C.; Guha, Sonia; O’Brien-Jenkins, Ann; Coffey, Erin E.; Campagno, Keith E.; McCaughey, Stuart A.; Laties, Alan M.; Carlsson, Leif G.; Mitchell, Claire H. (Frontiers in Pharmacology, 2018)
The accumulation of partially degraded lipid waste in lysosomal-related organelles may contribute to pathology in many aging diseases. The presence of these lipofuscin granules is particularly evident in the autofluorescent lysosome-associated organelles of the retinal pigmented epithelial (RPE) cells, and may be related to early stages of age-related macular degeneration (AMD). While lysosomal enzymes degrade material optimally at acidic pH levels, lysosomal pH is elevated in RPE cells from the ABCA4-/- mouse model of Stargardt’s disease, an early onset retinal degeneration. Lowering lysosomal pH through cAMP-dependent pathways decreases accumulation of autofluorescent material in RPE cells in vitro, but identification of an appropriate receptor is crucial for manipulating this pathway in vivo. As the P2Y12 receptor for ADP is coupled to the inhibitory Gi protein, we asked whether blocking the P2Y12 receptor with clinically-relevant antagonist ticagrelor could restore lysosomal acidity and reduce autofluorescence in compromised RPE cells from ABCA4-/- mice. Oral delivery of ticagrelor lowered lysosomal pH in these RPE cells. Ticagrelor also partially reduced autofluorescence in the RPE of ABCA4-/- mice. In vitro studies in ARPE-19 cells using more specific antagonists AR-C69931 and AR-C66096 confirmed the importance of the P2Y12 receptor for lowering lysosomal pH and reducing autofluorescence. These observations identify P2Y12 receptor inhibition as a potential target to lower lysosomal pH and clear lysosomal waste in RPE cells.